Cascade up-conversion of photoluminescence in quantum dot ensembles - Santos, João R. (2008)
We present a theoretical model and Monte Carlo simulation results that naturally explain all the features of the thermally activated photoluminescence upconversion effect also known as anti-Stokes photoluminescence ASPL observed in ensembles of colloidal semiconductor nanocrystal quantum dots QDs . The proposed ASPL mechanism includes the following principal ingredients: i optical-phonon-assisted absorption of an incident photon in a relatively large dot in the ensemble, ii emission of a higher-energy photon from the zero-phonon exciton-polaron state, with an upconversion equal to one optical-phonon energy, and iii cascade reabsorption and re-emission processes involving QDs of successively smaller sizes within the sample, rendering the experimentally observed large anti-Stokes shift of the energy of the photon that finally leaves the sample. The results obtained by the Monte Carlo modeling based on the proposed mechanism reproduce all the experimentally observed ASPL trends in colloidal QD solutions.